Determination of Carbapenemase-Producing OXA- 48 and KPC Genes in Antibiotic-Resistant Gram-Negative Bacilli Isolated from Infectious Samples of Cardiovascular Patients Hospitalized in Sari Fatemeh Al-Zahra Heart Hospital - Mina Owrang; Ebrahim Taheri Hossein Abad; Shakiba Shafaie (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Antibiotic resistance remains a serious problem for human health and continues to impact patients in hospitals worldwide. Carbapenem antibiotics are frequently used as the last line of treatment for infections caused by Gram-negative bacteria. The primary mechanism of resistance to carbapenems is the production of carbapenemase enzymes. This study aimed to determine the frequency of carbapenemase-encoding genes including OXA-48 and KPC, in antibiotic-resistant Gram-negative bacilli isolated from infectious samples collected from cardiovascular patients hospitalized in the wards of Fatemeh Al-Zahra Heart Hospital in Sari in 2022. Materials and methods: In this descriptive cross-sectional study, conducted from January 2022 to June 2022, 61 samples were collected from hospitalized cardiovascular patients. All bacterial isolates were identified using standard biochemical methods. The antimicrobial susceptibility pattern of the isolates was assessed using the disc diffusion test (DDT) in accordance with Clinical and Laboratory Standards Institute (CLSI) guidelines. Polymerase chain reaction (PCR) was employed to confirm the presence of OXA-48 and KPC genes. Results: A total of 61 clinical samples were analyzed. The most frequently collected samples from patients included urine (52.45%), trachea (29.50%), wound (11.47%), and surgical site secretions (3.27%). The most common types of bacteria isolated were E. coli (86.27%), Enterobacter (67.19%), Pseudomonas (67.19%), and Citrobacter (16.39%). Additionally, highest rates of bacterial resistance were observed against ceftazidime (100%) and imipenem (96.72%). The frequency of OXA-48-encoding genes was detected in 8 clinical isolates (13.11%). The bacteria harboring the OXA-48 gene exhibited 100% resistance to ceftazidime and imipenem. In contrast, the KPC gene was not detected in any of the isolates. Among the bacterial species analyzed, the highest frequency of the OXA-48 gene was observed in Enterobacter isolates. Conclusion: The present study demonstrates that the rate of drug resistance as well as the production of beta-lactamase enzymes, is significantly high in Gram-negative strains, including members of the Enterobacteriaceae family and Pseudomonas aeruginosa. As a result, the management and treatment of infections caused by these bacteria may pose substantial challenges.